Status quo, opportunities and challenges of integrated application of coal-to-hydrogen and CCUS technology in China - Xu Mao; Zhang Xian; Fan Jingli; Gao Lin; Xu Dong (矿业科学学报, 2021)
Against the background of addressing global climate change, hydrogen has attracted much attention because of its characteristics of being clean, carbon-free and efficient.In view of China's resource endowment, hydrogen demand and emission reduction demand, the integrated application of coal-to-hydrogen and carbon capture, utilization and storage(CCUS)technology is of great significance to China's low-carbon energy transformation.The development status, opportunities and challenges of integrated application of coal-to-hydrogen and CCUS technology in China were analyzed systematically in this study to provide relevant suggestions for the development of coal-to-hydrogen with low-carbon emission in China.The results showed that: ①Compared with other hydrogen production technologies, coal-to-hydrogen with CCUS has significant cost advantages; ②Compared with hydrogen production from renewable energy, carbon footprint is the weakness of coal-to-hydrogen, even though CCUS technology can reduce carbon emissions by about 90 %; ③Xinjiang, Shanxi, Shaanxi and Inner Mongolia can be the first areas to deploy coal-to-hydrogen with CCUS technology; ④The challenges of coal-to-hydrogen with CCUS mainly include lack of public recognition and the competition with renewable energy.In the future, China should strengthen the top-level design and publicity of coal-to-hydrogen with CCUS technology, actively promote the research, development and demonstration of coal-to-hydrogen with CCUS, so as to ensure the development of China's hydrogen industry.